Indulgences Akram Khan and Juliette Binoche - Hutera, Donald 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Akram Khan and Juliette Binoche. Khan's latest high-profile international touring duet was premiered at London's National Theatre, in-i unites him with the Oscar-winning French actress Juliette Binoche.